Vector-Reservoir Transmission in A Japanese Encephalitis Model - Lisa R. Sari; Puji Andayani; Sekarsari U. Wijaya (Indonesian Journal of Mathematics and Applications, 2023)
In this paper, a model for characterizing the dynamics of vector-borne diseases is put out, emphasizing Japanese encephalitis. The susceptible-infectious-recovered (SIR) model for the host population and the susceptible-infectious (SI) model for the vector and reservoir populations are used to examine the role of host-vector-reservoir dynamics and their interplay. The standard incidence rate represents the probability of an actual disease contact. The model has two equilibrium points: an endemic equilibrium point that only exists under specific circumstances and a disease-free equilibrium point that always exists. The stability analysis of the model’s equilibrium point has been established. The basic reproduction number is calculated using the next-generation matrix method. A sensitivity analysis on models supported by numerical simulations is provided to demonstrate the critical parameter that affects the spread of disease.Our findings indicate that vector-reservoir transmission is the primary cause of endemic. Controlling vector-reservoir transmission lowers the likelihood of human infection and creates disease-free settings.